The effect of retirement planning behaviour among working individual in Klang Valley / Ahmad 'Afi Izzuddin Amran - Amran, Ahmad 'Afi Izzuddin (Faculty of Business and Management, 2019)
Nowadays, the awareness level in retirement is still a vague issue among society in Malaysia. There are a tot of retirement products being introduced by the financial institutions and yet the initiatives to save for retirement are step sided by many employee. Since most of the employee think that companies and government retirement plan should be enough to cover up for their golden years expenses. Furthermore, many studies have shown that money saved in companies and government pension plan may not be adequate for the golden years. Therefore, this paper, subjectively, aimed at discussion on the effect of retirement planning behaviour among working individual in Klang Valey towards financial literacy, saving behaviour, personal attitude and goal clarity. As a result, a theoretical framework is developed to illustrate the relationship between demographic, financial literacy, saving behavior, personal attitude and goal clarity.